A new model for squirt-flow attenuation and dispersion in fluid-saturated rocks - Gurevich, Boris; Makarynska, Dina; Pervukhina, M.; De Paula, Osni (EAGE, 2009)
We develop a new simple model of squirt-flow model attenuation and dispersion, in which most parameters can be independently measured or estimated from measurements. The pore space of the rock is assumed to consist of stiff porosity and compliant (or soft) pores present at grain contacts. The effect of isotropically distributed soft pores is modeled by considering pressure relaxation in a disk-shaped gap between adjacent grains. This derivation gives the complex and frequency-dependent effective bulk and shear moduli of a rock, in which the soft pores are liquid-saturated and stiff pores are dry. The resulting squirt model is consistent with Gassmann s and Mavko-Jizba equations at low and high frequencies, respectively.